2016
DOI: 10.1080/10773525.2016.1214795
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health effects of occupational exposure to charcoal dust in Namibia

Abstract: Background: Charcoal processing activities can increase the risk of adverse respiratory outcomes. Objective: To determine dose-response relationships between occupational exposure to charcoal dust, respiratory symptoms and lung function among charcoal-processing workers in Namibia. Methods: A cross-sectional study was conducted with 307 workers from charcoal factories in Namibia. All respondents completed interviewer-administered questionnaires. Spirometry was performed, ambient and respirable dust levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…BC is resistant to chemical transformation (Forbes et al, 2006;Petzold et al, 2013). As a component of fine PM, BC potentially has an adverse effect on human health (Janssen et al, 2011;Hamatui et al, 2016). It can aggravate existing illnesses and increase the morbidity and hospital admissions as well as mortality from cardiovascular and respiratory diseases and from lung cancer (Fullerton et al, 2008).…”
Section: The Charcoal Supply Chain In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…BC is resistant to chemical transformation (Forbes et al, 2006;Petzold et al, 2013). As a component of fine PM, BC potentially has an adverse effect on human health (Janssen et al, 2011;Hamatui et al, 2016). It can aggravate existing illnesses and increase the morbidity and hospital admissions as well as mortality from cardiovascular and respiratory diseases and from lung cancer (Fullerton et al, 2008).…”
Section: The Charcoal Supply Chain In Africamentioning
confidence: 99%
“…Organic carbon (OC), also called organic aerosol (OA), is a significant fraction of PM throughout the world and so affect human health (Hamatui et al, 2016). Its fraction of the total PM depends on location.…”
Section: The Charcoal Supply Chain In Africamentioning
confidence: 99%
“…Smoking behavior is one of the factors that cause respiratory disorders (22). Research in Namibia showed that smoking behavior is associated with adverse effects on lung function (40). It is associated with a decrease in the spirometry index of lung function (41).…”
Section: Meta-analysis Of Smoking Habits In Association With Abnormal...mentioning
confidence: 99%
“…Occupational exposures were another important source of ambient air pollution exposure. Activities included limestone processing in Zambia (Bwalya et al, 2011), exposure to desert dust in West Africa [reviewed by de Longueville et al (2013)], traffic exhaust (DeMarini, 2013), dust and fumes in artisanal mining (Ekosse, 2011), city transit-related air pollution Ekpenyong et al, 2012), stone quarrying industry exposures including deposition of inhaled aerosol particles at an industrial site in Egypt (Furi et al, 2017), sulfur dioxide (SO2) emissions from platinum group metal (PGM) smelting in Zimbabwe (Gwimbi, 2017), and charcoal processing activities in Namibia, including exposure to charcoal dust (Hamatui et al, 2016). DNA adducts to measure air pollution exposure among urban and suburban residents was also implemented in some studies (Ayi-Fanou et al, 2011).…”
Section: Exposures Measuredmentioning
confidence: 99%